ASSESSMENT OF TECHNICAL CONDITION AND REINFORCEMENT OF STRUCTURES ARCHITECTURAL MONUMENT "BUKHARA WATER TOWER" - Vakhidov M.M. , Safarov U.I. (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The article examines the state of the Bukhara water tower, built from an interesting rod mechanical system. In order to use the architectural monument for tourism, the structure of the structure has been studied, constructive solutions have been developed to strengthen it, improve the strength, reliability and durability of the tower.